Meningkatkan Kemampuan Motorik Halus Melalui Penerapan Kegiatan Project Based Learning pada Anak Kelompok B-2 TK Negeri Pembina Mataram - Yulia Era Fazira; Ika Rachmayani; Gigih Aprianti (Indonesian Publication Center, 2023)
Problems of early childhood in fine motor skills in group B-2 Mataram Pembina State Kindergarten, Mataram city have not developed properly. Therefore, research was carried out using the Project Based Learning (PJBL) learning model with the aim of knowing whether there was an increase in fine motor skills in early childhood in Group B-2 TK Negeri Pembina Mataram, Mataram city. This type of research is Classroom Action Research (PTK) which is carried out in three cycles. Based on the results of improvement research carried out in order to improve fine motor skills of early childhood by applying the Project Based Learning (PJBL) learning model, an increase in children's learning activities in writing activities was obtained. At the end of cycle 1, the success of children in developing children's fine motor skills, namely 43% of children who achieved the acquisition of indicators of fine motor skills. For cycle 2, the success of the children reached as many as 68% of the children who achieved the ability to acquire fine motor indicators. Whereas for cycle 3, 88% of the children were able to achieve the fine motor mastery criteria. From the implementation of the third cycle of this study, it can be seen that there has been an increase for each cycle and based on the research completeness criteria, that is, more than 75% of children have achieved the expected criteria in the study. For this reason, it can be concluded that the Project Based Learning (PJBL) learning model can improve children's fine motor skills.